Estimated Aerosol Health and Radiative Effects of the Residential Coal Ban in the Beijing-Tianjin-Hebei Region of China - Kelsey R. Bilsback; Jill Baumgartner; Michael Cheeseman; Bonne Ford; John K. Kodros; Xiaoying Li; Emily Ramnarine; Shu Tao; Yuanxun Zhang; Ellison Carter; Jeffrey R Pierce (Aerosol and Air Quality Research)
Abstract Particle-phase air pollution is a leading risk factor for premature death globally and impacts climate by scattering or absorbing radiation and changing cloud properties. Within the Beijing-Tianjin-Hebei region of China, where there are severe air quality problems, several municipalities have begun implementing a coal-to-electricity program that bans residential coal and provides subsidies for electricity and electric-powered heat pumps. We used GEOS-Chem to evaluate two complete residential coal-to-electricity transitions—a Beijing-off scenario and Beijing-Tianjin-Hebei-off scenario—each relative to a base case. We estimate that within China, the ambient fine particulate matter (PM2.5) reductions in the Beijing-off scenario could lead to 1,900 (95% CI: 1,200−2,700) premature deaths avoided annually, while the Beijing-Tianjin-Hebei-off scenario could lead to 13,700 (95% CI: 8,900−19,600) premature deaths avoided annually. Additionally, we estimate that the residential-coal-ban scenarios will result in a positive top-of-the-atmosphere aerosol direct radiative effect (DRE) (model domain average: Beijing-off: 0.023 W m−2; Beijing-Tianjin-Hebei-off: 0.30 W m−2) and a negligible cloud-albedo aerosol indirect effect (AIE) (Beijing-off: 0.0001 W m−2; Beijing-Tianjin-Hebei-off: 0.0027 W m−2). To evaluate the uncertainty of the radiative effects, we calculated the DRE under four black-carbon mixing-state assumptions and both the DRE and AIE assuming three different black-carbon-to-organic-aerosol (BC:OA) ratios for residential-coal emissions. Although the magnitude of our radiative forcing estimates varied across sensitivity cases, the domain average remained positive. When only considering the aerosol-related effects of the aforementioned coal-ban scenarios, we predict substantial health benefits, but do not anticipate a climate “co-benefit”, because removing aerosol emissions leads to a warming tendency. However, if the coal-to-electricity program results in less net greenhouse gas emissions due to the replacement heaters, the policy may be able to achieve health and climate “co-benefits”.